2019
DOI: 10.3389/fmars.2019.00737
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Marine Heatwaves With Sub-Optimal Data

Abstract: Marine heatwaves (MHWs), or prolonged periods of anomalously warm sea water temperature, have been increasing in duration and intensity globally for decades. However, there are many coastal, oceanic, polar, and sub-surface regions where our ability to detect MHWs is uncertain due to limited high quality data. Here, we investigate the effect that short time series length, missing data, or linear long-term temperature trends may have on the detection of MHWs. We show that MHWs detected in time series as short as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…This would, however, require more details and certain restrictions. Studies focusing on other climate events, such as marine heatwaves (Hobday et al ., 2016), also suggest that the application of annual daily data can significantly increase the robustness of generated events' characteristics in different time scales (Schlegel et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This would, however, require more details and certain restrictions. Studies focusing on other climate events, such as marine heatwaves (Hobday et al ., 2016), also suggest that the application of annual daily data can significantly increase the robustness of generated events' characteristics in different time scales (Schlegel et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the data time period needs to be sufficiently long for estimating a climatology (ideally a minimum of 30 years; e.g., WMO 2018). However, Schlegel et al (2019) showed that as few as 10 years of data may be sufficient for constraining the climatology, and recent studies have used fewer data, from short records or those with temporal gaps, to identify MHWs (e.g., Oliver et al 2017).…”
Section: Available Data Setsmentioning
confidence: 99%
“…On the other hand, decades of measurements are needed to establish a well‐defined baseline for distinguishing marine heatwave impacts from interannual variability (Hobday et al., 2016). Although a recent study provides best practice for detecting marine heatwaves with limited temperature data (Schlegel, Oliver, Hobday, & Smit, 2019), it is unknown whether the assessment of marine heatwave impacts can be well established with limited biogeochemical data. Hence, at present, we consider that having such long‐term and high‐resolution measurements is essential to develop a mechanistic understanding of the effects of marine heatwaves on ocean biogeochemistry.…”
Section: Introductionmentioning
confidence: 99%